Impact of marina construction on scleractinian corals in Kampung Tekek, Tioman Island, Malaysia / Nikoo Cheheltani - Cheheltani, Nikoo (2011)

(untitled)
This study was conducted to determine the impacts of newly constructed marina on the adjacent coral reefs in Kampung Tekek, Tioman Island. Two study sites were chosen, consisting of the fringing coral reef adjacent to the constructed marina and a control site 3 nm south which was the fringing coral reef around Pulau Renggis (Pulau=Island). Acute and chronic impacts in two depths (shallow, <6 m and deep, 6-12 m) at the Marina site were studied. To document impacts of the construction, substrate cover percentage and environmental parameters such as sedimentation rate and sediment type were measured. In addition, changes in physiological aspects were monitored on four different coral growth forms. The acute impact study using modified Reef Check showed that there were some negative changes such as coral breakage and increased sand cover (from 6.88% to 22.50 %) and silt cover (from 0% to 16.25%). Differences in substrate cover before and after construction were detected in deep water with higher Recently Killed Corals (%) and shallow water with higher Rubble (%). The chronic impacts study showed that there was a significant difference (F: 6.735, p<0.05) in sedimentation rate between Marina site (up to mean of 23.37 mg/cm²day in Marina Shallow) and control site at Renggis (mean of 0.59 mg/cm²day). The higher sedimentation rate recorded in Marina site significantly decreased the light intensity to a daily mean of 275.15 Lux. Coral cover % was lower in Marina site (with the lowest average of 24.74 %) compared to control site (53.27 %). Comparison between shallow and deep areas in Marina site showed that Marina Deep was the most affected due to high sedimentation and its lower light intensity. Changes in zooxanthellae density and chlorophyll content of the selected scleractinian coral growth forms indicated that the corals had been under stress due to smothering by sediments in Marina site. Foliose growth form showed more changes in their physiological aspects compared to other iv growth forms. Results of this study demonstrated some negative acute and chronic impacts of the marina construction to the adjacent coral reef. Therefore management programs should be improved so as to prevent or at least reduce the impacts of similar constructions at the vicinity of sensitive habitats in the future.